Thermal degradation and tensile strength of sansevieria trifasciata-polypropylene composites. Issue 1 (June 2015) - Abral, H; Kenedy, E
Abstract: The paper exhibits thermal degradation and tensile strength of Sansevieria Trifasciata (ST) fibers and polypropylene (PP) composites. Thermal degradation of ST fibers PP composites was conducted by using thermogravimetry (TGA) instrument, meanwhile tensile strength of the composite was done by using tensile equipment. The results show that the thermal resistance of ST fibers PP composites was higher than that of virgin PP only. Increases in volume fraction of fibers in the composites enhance the tensile strength. Scanning Electron Microscope (SEM) observation exhibits good interface bonding between ST fibers and PP matrix.